Analysis of energy use and CO 2 emission in service industries: Evidence from Sweden (2012)
This study analyses the trends in energy use and CO2 emissions for 19 sub-sectors in the Swedish service sectors following the classification of the International Standard Industrial Classification of all Economic Activities (ISIC) at the 2-digit level of aggregation over the period 1993–2008. This empirical study intends to examine energy use, energy efficiency and CO2 emissions using data envelopment analysis (DEA) and panel data techniques. DEA is applied to assess energy efficiency within a production framework. Panel data techniques are used to determine which variables influence energy efficiency. The results show that Swedish services industries have increased energy consumption and CO2 emissions in the period 1993–2008. The results from the DEA show significant variation in energy efficiency across service industries. The results also indicate that this sector has increased technical efficiency and energy efficiency while decreasing CO2 emissions, especially in the later years of our sample period. The results of panel data techniques show that higher energy taxes, electricity consumption, investments and labour productivity generate higher energy efficiency, while higher fossil fuel consumption leads to lower energy efficiency. All findings of this study are important for developing effective energy policies that encourage better energy use and energy management in the service industries.